Managing human resources in the human services supervisory challenges - Perlmutter, Felice Davidson, 1931-; Bailey, Darlyne, 1952-; Netting, F. Ellen (New York ; Oxford : Oxford University Press, 2001)
In the context of our changing environment, this book focuses on specific managerial skills required for successful supervision. It defines dilemmas, paradoxes and challenges faced by supervisors, and offers case illustrations of approaches.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Human services personnel -- Supervision of -- United States; Personnel management -- United States